2015
DOI: 10.1177/2325967115s00021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Osteochondritis Dissecans Of The Capitellum In Young Baseball Players Based On Ultrasonographic Findings

Abstract: Objectives:Osteochondritis dissecans (OCD) of the capitellum is a well-recognized cause of elbow pain and disability in adolescent athletes. However, little is known about the prevalence of OCD in adolescent baseball players. This study aimed to determine the prevalence of OCD in baseball players aged 10-12 years based on ultrasonographic findings and to investigate the clinical characteristics of those with OCD lesions.Methods:A total of 1,040 players aged 10-12 years completed a questionnaire, ultrasound ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 0 publications
0
34
0
2
Order By: Relevance
“…En cambio,fue ampliamente tratada por la literatura clínica del comportamiento corporal de los deportistas (e.g. Kida et al 2014;Matsuura et al 2014) debido a que las lesiones en esta articulación suelen estar asociadas con el movimiento de lanzamiento (Guerra y Timmerman 1996). En este caso se trata de un individuo masculino, con dieta predominantemente terrestre.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En cambio,fue ampliamente tratada por la literatura clínica del comportamiento corporal de los deportistas (e.g. Kida et al 2014;Matsuura et al 2014) debido a que las lesiones en esta articulación suelen estar asociadas con el movimiento de lanzamiento (Guerra y Timmerman 1996). En este caso se trata de un individuo masculino, con dieta predominantemente terrestre.…”
Section: Discussionunclassified
“…Estos últimos explicarían la alta prevalencia de este tipo de lesiones en atletas de alto rendimiento (Aichroth 1971;Cahill 1995;Takahara et al 1999). Por ejemplo, puede alcanzar entre un 2,1% (Matsuura et al 2014) y un 3,4% en la tróclea del húmero en jugadores de béisbol (Kida et al 2014). En cambio, en poblaciones no asociadas con la actividad física deportiva las frecuencias de OCD son menores, alcanzando por ejemplo entre un 0,01 y un 0,06% en el caso de la rodilla (Lindén 1976;Petersen et al 2006;Solomon et al 2010).…”
Section: Terminología Patogénesis Y Epidemiología General De La Ocdunclassified
“…Matsuura et al (10) reported that the prevalence of OCD of the capitellum on ultrasonography in 1040 young baseball players (mean age, 10.7 years ; range, 10 -12 years) was 2.1%. Our results (1.6%) were lower than that reported by Matsuura et al (10), and the cause seemed to be the inclusion of all elementary school students in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We defined grade 1a, 2, and 3 as abnormal findings. Grade 1b was not considered abnormal because Matsuura et al (10) reported that cystic appearance of the subchondral bone surface was thought to be a variation of normal development during ossification.…”
Section: Ultrasonographic Findings Of the Capitellummentioning
confidence: 99%
See 1 more Smart Citation